Investigation of damage characteristics in freeze-thawed grey-white sandstone using AE multifractal analysis - Xinlei Zhang; Xiaoli Liu; Jiaxu Jin; Haibo Wang; Zhiqiang Lv; Yong Xiao (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract The freeze–thaw (F-T) process in high-altitude rocks is a critical factor influencing the stability of engineering structures in such environments. Grey-white sandstone, fully saturated with water, was subjected to repeated F-T cycles to investigate its behavior under uniaxial compression. Acoustic emission (AE) tests were conducted following these cycles, and multifractal theory was applied to evaluate the impact of F-T cycles on the rock's macroscopic mechanical properties, AE characteristics, three-dimensional AE localization distribution, and multifractal behavior. Results indicate that as the number of F-T cycles increases, the compressive strength and loading duration of the sandstone decrease significantly. This reduction is accompanied by an earlier onset of fluctuations in the ringing count rate and an upward trend in the dynamic b-value curve. Additionally, the fracture mode shifts from shear-dominated to tension-dominated failure. A close correlation was observed between the spatial distribution of AE localization points and the macroscopic cracking patterns. The sudden increase in Δα and the sudden drop in Δf(α) in multifractal parameters can serve as precursors for the instability warning of freeze-thawed rocks. As the number of F-T cycles increases, the width of the multifractal spectrum Δα increases, Δf(α) decreases, and the sudden increase in Δα and the sudden drop in Δf(α) in the time-varying dynamic curves of multifractal parameters occur earlier. This study provides important theoretical support and technical reference for damage monitoring and stability assessment in geotechnical engineering in cold regions.